Does CSR affect investment efficiency? The moderating role of company reputation - Sharmina Afrin; Md. Mominur Rahman (PSU Research Review)
Purpose – The purpose of the paper is to investigate the association between corporate social responsibility (CSR) and investment efficiency (INE) in Bangladeshi pharmaceutical companies and to explore the moderating role of corporate reputation in this relationship. Design/methodology/approach – The paper employs a two-step method, with stage 1 involving the development of a theoretical model using the literature's strategic framework and stage 2 using structural equation modelling (SEM) to investigate the relationships between variables. The data set used in the analysis includes 296 responses from senior executives/managers and subordinates at Bangladeshi pharmaceutical firms. Findings – The study finds that CSR activities that focus on customers, employees and the community significantly affect INE, as well as the extended stakeholders, and that company reputation moderates this relationship. The effect of CSR on INE differs between well-established companies and business firms with favourable reputations. Practical implications – The paper contributes to understanding the relationship between CSR and INE in a developing country context and highlights the importance of corporate reputation in this relationship. The findings suggest that companies can enhance their INE through CSR initiatives and that a positive reputation can strengthen this relationship further. Originality/value – The study adds to the limited literature on CSR and INE in developing countries and provides new insights into the moderating role of corporate reputation in this relationship.